Promoting a culture of openness: Institutional open access policy development and review at a Canadian university - Zerkee, Jennifer; Moore, Alison J.; Shuttleworth, Kate; Dowson, Rebecca; Bird, Gwen (Partnership, 2021)
Institutional open access (OA) policies can act as a solid foundation on which to build university-wide support for open access. This is the first paper to reflect on the entire process of developing, implementing, and reviewing an institutional open access policy at a Canadian post-secondary institution. Simon Fraser University (SFU) is one of a few Canadian universities with an institutional open access policy. As a leader in open access, SFU is well positioned to share observations of our experiences in the first three years of our OA policy. Throughout this paper, we reflect on the role that the policy plays in the broader culture of openness at SFU and on the OA resources and supports provided to SFU researchers. Other institutions may find our observations and adoption of the SOAR (strengths, opportunities, aspirations, results) appreciative inquiry framework useful as they explore future policy development or review and work to promote a culture of open access within their university community.